Political praxis and morality in Machiavelli’s Prince - Monz´on Pedroso, Odar Edilberto (2024)
The main problem of this research raises the fact that the prince’s scholars argue, to a greater or lesser extent, that the thesis Machiavelli recommended the immorality as a general principle in political praxis. Our objective is to determine if Machiavelli recommended the immorality as a general principle in political praxis. Our hypothesis is that Machiavelli didn’t recommend the immorality as a general principle in political praxis. That is, the father of political science recommended that in political praxis morality should be the rule and immorality should be the exception.